Pengenalan Gestur Jari Menggunakan Pengolahan Citra untuk Mengendalikan Joint pada Base Robot Lengan - Ali Rizal Chaidir; Wahyu Muldayani; Guido Dias Kalandro (Jurnal Rekayasa Elektrika, 2018)
The Robot is a technology that can help human to do daily activities. One type of robot is an arm robot, arm robot can work automatically, manually, and a combination of both. Some techniques that can be used to give commands to the robot are to use hand and finger gestures, to do the techniques can utilize the vision machine. One of the advantages of using a vision machine is that it does not require many electronic components to recognize hand and finger gestures. The focus of this research is to implement a camera to recognize the operator’s finger gestures so that the gesture can give commands to the robot. The camera captures the image of operator's finger, the image is a process inside the computer to obtain the pixel coordinate parameters of the index fingertip and right lower pixel of the image, and then the angle obtained from both coordinates using trigonometric equations. The result is that the robot can follow the movement of the finger when the angle between 30° to 150°.